IMPLEMENTASI METODA MATRIX BERBASIS DISKRIT UNTUK MENDETEKSI OBYEK BERGERAK DI DALAM AIR - Purwanto, Purwanto; Achlison, Unang (ELKOM : JURNAL ELEKTRONIKA DAN KOMPUTER, 2019)
Number of fish seed can be measured by means of conventional observation using eye senses. But when the fish seed measured pretty much it will take a long time (not efficient) and cause incorrect measurement results (inaccurate). The accuracy of calculation of fingerlings is crucial trust between seller and buyer. During this time a sensor is used to detect the amount of fish seed is passed through a transparent hose using a light sensor (Light Dependent Resistor) and photodiode sensors as infra red light receiver. The level of accuracy of the sensor lies in the intensity of the light beam is received so that the sensor will be impaired if airya murky and there are air bubbles pass through the sensor so that the fish count error occurs. This research will be conducted design counters the number of fingerlings using infra red phototransistor sensor with a frequency of 20KHz to fish and then processed using the logic matrix. Results matrix logic into the data input to be processed by a microcontroller as the basis of results of calculation of the amount of fish. Development model studies using models of R & D (research and development) that produce a product in the form of the final product. Experiments were carried out using the type and length of catfish fingerlings with a length of 3 cm to 5 cm. Fish seed count tool has been tested to catfish farmers in the village Siwarak Ungaran City. The trial results calculators fish seeds have difference of 3% of the calculated results Manual or accuracy of calculation results have fish reaches 97%, then a counter of fish seed is acceptable to be used by catfish farmers. Keywords: calculating the number of fingerlings, matrix logic NAND, Microcontroller